2010
DOI: 10.1111/j.1574-6941.2010.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in developmental life-history traits of the bacterium Myxococcus xanthus

Abstract: The soil bacterium Myxococcus xanthus is a model for the study of cooperative microbial behaviours such as social motility and fruiting body formation. Several M. xanthus developmental traits that are frequently quantified for laboratory strains are likely to be significant components of fitness in natural populations, yet little is known about the degree such traits vary in the wild and may therefore be subject to natural selection. Here we have tested whether several key M. xanthus developmental life-history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…3A and Table S3; Kruskal Wallis-test: P < 0.001). This result is consistent with previous work that documented extensive variation in several developmental phenotypes among natural M. xanthus isolates (34,36,42,48).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…3A and Table S3; Kruskal Wallis-test: P < 0.001). This result is consistent with previous work that documented extensive variation in several developmental phenotypes among natural M. xanthus isolates (34,36,42,48).…”
Section: Resultssupporting
confidence: 93%
“…1A) (45) and several developmental phenotypes, including spore production (Fig. 3A), the rate of development, responsiveness to nutrient depletion in triggering development (42), and competitiveness in forced isolate pairings (36). Here we have now also shown that pronounced social variation is present at high frequencies within many natural fruiting bodies-indeed within a majority of those fruiting bodies sampled here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These subsets include clones that exhibited significant within-fruiting-body variation in swarming rate, spore production or both. Social trait phenotypes vary continuously in natural populations of M. xanthus [14,20,21,[40][41][42][43]. Nonetheless, we found previously that subsets of isolate samples from a single fruiting body often cluster, apparently discretely, within significantly different social phenotype ranges in a manner detectable by a k-means cluster algorithm [14].…”
Section: Materials and Methods (A) Clonesmentioning
confidence: 84%
“…Naturally variable traits include developmental competitiveness in mixed groups [11,27,42], social swarming rates [20], rate of development [21], allee effects during development [43] and predation range [40]. Kraemer & Velicer [14] found that even closely related clones isolated from within a single fruiting body often vary markedly in their expression of social phenotypes.…”
Section: Introductionmentioning
confidence: 99%